Sweat and blood : a history of U.S. labor unions - Skurzynski, Gloria (People's history, 2009)
Examines the history of labor unions in the United States, and describes the conditions faced by the early worker force, which was made up of settlers and immigrants, and also covers strikes and the famous strike leaders.